Revisoría fiscal en temas de corrupción (2023)
A financial crime or fraud can be conceived as the distortion of financial information in order to cause harm or harm to third parties who have contact with it. (EAFIT University, 2023). Colombia has experienced different cases of embezzlement or financial crimes in recent years, one of the most important has been the case of Saludcoop EPS, which at the time, was one of the most powerful entities in the country, classified as one of the 20 largest companies in Colombia. However, the entity made bad economic decisions, which is why it committed a financial embezzlement, which is still affecting the Colombian economy today. Through this document, different factors will be analyzed, such as the reasons why Saludcoop had to be intervened by Colombian control entities and the consequences that their decisions generated in the health system of the country.